Cultural evolution, economic growth and human welfare: A drift process? - Ulrich Witt (Max Planck Institute of Economics, 2012)
To assess whether and when the equation economic growth = better life holds, it is necessary to understand what human motivations drive the economic growth process. The preference subjectivism of canonical welfare economics is of little help here as it treats the motivations underlying individual behavior as an unexplained black box. The present paper therefore reviews several motivational hypotheses suggested by biology, behavioral science, and cognitive psychology. They point to a strong influence of cognitive and noncognitive learning processes on the underlying motivations or, in economic terminology, the emergence and change of individual preferences. As a consequence, subjective welfare assessments tend to follow a drift process once a certain level of prosperity has been accomplished by economic growth. The normative relevance of the resulting preference relativism is argued to be particularly momentous, if the value basis of normative judgments is extended beyond the welfare criterion to justice and fairness considerations.
Keywords: 330; Präferenztheorie; Verhaltensökonomik; Kognition; Reichtum; Wirtschaftswachstum; Sozialer Wandel